A Rare Case of Chylothorax due to Pulmonary Lymphangiectasia in a 7-Year-Old Boy - Ruggeri, Giovanni; Destro, Francesca; Maffi, Michela; Gregori, Giulio; Lima, Mario (European Journal of Pediatric Surgery Reports, 2013)
Pulmonary lymphangiectasia (PL) is a rare condition characterized by dilatation of the lymphatic vessels. Post-neonatal PL is usually associated with pleural effusion and should therefore be suspected in the presence of chylothorax. We describe a post-neonatal manifestation of PL in a 7-year-old boy presenting chylothorax. Radiological examinations included thorax X-ray, ultrasound, and computed tomography scans. After the failure of conservative management (maintenance of the chest tube, total parenteral nutrition, administration of somatostatin synthetic analogues) we performed a thoracoscopic massive ligation of the thoracic duct's collateral along with a lung biopsy. Histology was compatible with type 1 congenital pulmonary lymphangectasia. One month after surgery a thoracoscopic pleurodesis was required for persistent chylothorax. The boy is now doing well 1 year after surgery.
Keywords: pulmonary lymphangiectasia; chylothorax; thoracoscopy